2009
DOI: 10.1002/ibd.20949
|View full text |Cite
|
Sign up to set email alerts
|

Magnifying colonoscopy used to predict disease relapse in patients with quiescent ulcerative colitis

Abstract: The findings of magnifying colonoscopy in patients with quiescent UC is useful for predicting relapse and is associated with histological grade of inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Watanabe et al reported that the magnify-regular group, as mentioned above, had the significant lower relapse rate within 12 months compared to the magnify-irregular and magnify-defect group [7]. In the other study, UC relapse during 12 months of follow-up was found to be increased with worsening grade by the 4 ME classifications [6].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Watanabe et al reported that the magnify-regular group, as mentioned above, had the significant lower relapse rate within 12 months compared to the magnify-irregular and magnify-defect group [7]. In the other study, UC relapse during 12 months of follow-up was found to be increased with worsening grade by the 4 ME classifications [6].…”
Section: Discussionmentioning
confidence: 95%
“…In the similar way using the indigo carmine spray, there was a report on the modified 6-grading system by adding the ME appearance of polypoid mucosal tags [13]. A recent study claimed the 3-grading system of ME findings with the indigo carmine spray consisting of magnify-regular, magnify-irregular, and magnify-defect in patients with the inactive disease [7]. On the other hand, Nishio et al classified the ME features after staining with an absorptive dye, methylene blue into 4 grades in the rectal mucosa of inactive UC patients [6], similar to the present study where crystal violet was employed as the absorptive dye.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regular pit pattern seen under MC is associated with a significantly reduced risk of relapse[9,10]. Patients with distorted MVP, abnormalities in epithelium or pit pattern have a higher grade of inflammation on histology and relapse subsequently[9-11,46,47]. In one recent study MC with NBI-lead target biopsies seems to predict long term outcomes[48].…”
Section: Does Endoscopy Predict Disease Relapse?mentioning
confidence: 99%
“…Histologically active disease is associated with greater risk of subsequent relapse[6-8]. Studies using standard WLE fail to predict relapse in quiescent UC[5,7,8], whereas studies using advanced endoscopic imaging modalities seem to hold promise[9-11]. …”
Section: Introductionmentioning
confidence: 99%